Fever and Its Treatment Among the More and Less Poor in Sub-Saharan Africa - Filmer, Deon (World Bank, Washington, D.C., 2013)
The author empirically explores the relationship between household poverty and the incidence and treatment of fever--as an indicator of malaria--among children in Sub-Saharan Africa. He uses household Demographic and Health Survey data collected in the 1990s from 22 countries in which malaria is prevalent. The analysis reveals a positive, but weak, association between reported fever and poverty. The geographic association becomes insignificant, however, after controlling for the mother's education. There is some evidence that higher levels of wealth in other households in the cluster in which the household lives are associated with lower levels of reported fever in Eastern and Southern Africa. Poverty and the type of care sought for an episode of fever are significantly associated: wealthier households are substantially more likely to seek care in the modern health sector. In Central and Western Africa those from richer households are more likely to seek care from all types of sources: government hospitals, lower-level public facilities such as health clinics, as well as private sources. In Eastern and Southern Africa the rich are primarily more likely to seek care from private facilities. In both regions there is substantial use of private facilities--use that increases with wealth. Like the incidence of fever, treatment-seeking behavior is strongly associated with the level of wealth in the cluster in which the child lives.